Examining how Supplier Relationships Affect Production and Performance, Specifically Collaborative Supplier Relationships: A Case Study of Letz Talk Technologies Ltd Uganda - Ninah Baseka (Uganda Christian University, 2023)
The purpose of the study aimed at examining how supplier relationships affect production and performance, especially collaborative supplier relationships basing on the following objectives; To establish the understanding of the respondents in terms of, relationship, age, gender, education level, position in the organization, number of years worked, and the marital status, o establish the different supplier relationship types of Letz Talk Technologies, To establish the level of supplier and production relationship Letz Talk Technologies , To establish the relationship between supplier, relationship Management and business production of Letz Talk products. Both qualitative and quantitative research designs were used. The sample size was randomly selected using the simple random sampling design. And sample size of 40 respondents was considered. Secondary sources of information included textbooks, magazines, pamphlets, research reports, journals, internet and newsletter were used in addition to various company annual reports, and Primary data was collected by the use questionnaires given by the respondents. Besides that, after collecting data, it was analysed in line with the problem, objectives of the research, research questions and other information especially from the literature review, Frequency tables and graphs were worked out basing on the data entered into excel. In these frequency tables and graphs, analysis was done with a corresponding percentage. Findings revealed that Letz talk technologies Ltd has important relationships with its suppliers whom they have closely worked with for years. The relationships are mostly collaborative and strategic which adds value to the company. Letz talk technologies is committed to the contractual arrangements though there is need to check on bureaucracy which sometimes stagnates and delays decision making and operations. Besides that, there is a lot of work in progress, a lot of bottlenecks were observed at the company and Suppliers take a lot of time in delivering what is requieed, It was recommended that Letz talk technologies Ltd should consider integration as a way to manage supplier problems and cut out the middle man to save time.
This is a dissertation.